Eficienţa liniilor electrice aeriene compacte dirijate - Postolaty V.M.; Bykova E.V.; Suslov V.M.; Shakaryan Y.G.; Timashova L.V.; Kareva S.N. (Problems of the Regional Energetics)
The basic theoretical principles to create co mpact controlled transmission lines are analyzed in the paper. The results of technical and project el aboration of some variants of such type of power transmission lines are presented and the comparison between their technical and economic indicators with those of traditional power transmission lines a nd foreign analogues is made in the paper. The efficiency of compact controlled transmission lines application to form power systems and to create intersystem ties as well as distribution electric network is also stated in the paper.